Import Competition, Heterogeneous Preferences of Managers, and Productivity - Cheng Chen; Claudia Steinwender (Center for Economic Studies and ifo Institute (CESifo), 2019)
When managers have objectives beyond maximizing monetary profits, inefficiencies may arise. An increase in competition may then force managers to improve the productivity of the firm in order to ensure survival. While this hypothesis has received ample theoretical attention, empirical evidence is scarce, mainly because preferences of managers are typically unobserved. In this paper, we exploit the fact that a large literature has documented specific non-monetary preferences of family managers. Using Spanish firm-level data, we compare how family-managed and professionally-managed firms react to import competition shocks. We find that import competition leads to productivity increases in family-managed firms that are initially unproductive. Productivity improvements are driven by family management as opposed to family ownership or non-managing family members. Furthermore, we show that these managers increase efficiency by reducing material usage, which is consistent with them trying to increase their short-term cash flow in order to survive. Finally, productivity improvements seem to be particularly pronounced in multi-generational family firms that also introduce organizational changes.
Keywords: D22; D23; F14; L21; L22; 330; import competition; productivity; family firms; managers